Administrația Chișinăului interbelic: tendințe de modernizare [Articol] - Xenofontov, Ion Valer (Lexon-Prim, 2023)
The scientific article is based on archival documents, the press of the time, iconographic sources, memoirs and literature. The author concludes that Bucharest has shown distrust in the representatives of the old Russian administration of Chisinau. At the same time, there was reluctance on the part of the former officials, who did not speak Romanian and were unfamiliar with the new requirements of the Romanian state. Litigation, corruption and failed attempts to modernise the city were not foreign to the municipal administration.
The administration in interwar Chisinau: modernization trends
Keywords: Chișinău istoria; interwar period; administrația Chișinăului; municipal administration